2015
DOI: 10.1007/s11934-015-0521-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Patient Population for MP-MRI and Fusion Biopsy for Prostate Cancer Detection

Abstract: The diagnosis and treatment of prostate cancer continue to evolve with advances in science and technology. The utilization of multiparametric MRI (mp-MRI) to identify lesions in the prostate has given clinicians the ability to visualize malignancy in the prostate with greater confidence. With this new ability came the advancement of fusion biopsy platforms, which allow for direct targeting of these lesions. As with any new technology in medicine, the proper use of these modalities and how they fit into current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…MP-MRI allows for imaging-based identification and characterization of PCa, improving diagnostic accuracy [ 13 , 14 ]. Yet, few studies have determined the value of MP-MRI as a non-invasive means for the prediction of BCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MP-MRI allows for imaging-based identification and characterization of PCa, improving diagnostic accuracy [ 13 , 14 ]. Yet, few studies have determined the value of MP-MRI as a non-invasive means for the prediction of BCR.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in multiparametric MRI (MP-MRI), consisting of T2-weighted (T2W), diffusion-weighted (DW), and dynamic contrast enhanced (DCE) imaging have improved detection and localization of clinically significant PCa [ 13 , 14 ]. Although MP-MRI has been extensively studied for its diagnostic capabilities, its significance in predicting postoperative outcomes is less well understood [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The future of fusion biopsy technologies seems promising; significant investment in commercially available fusion platforms continues and adoption is expanding. The challenge we face is appropriate utilization in the patient population that will benefit the most (64, 65). …”
Section: Discussionmentioning
confidence: 99%
“…Fusion biopsy, however, is a non-disruptive advance over the standard TRUS technique, is logistically simpler than the direct method, and clinical studies have already shown approx. 30% increase in the detection of high-risk cancers than untargeted methods [8, 9]. However, targeting accuracy relative to MRI is unknown, and it remains questionable if this method is sufficiently accurate.…”
Section: Introductionmentioning
confidence: 99%